Modified lithium titanate composite material for lithium ion battery and preparation method of modified lithium titanate composite material
Through the preparation of graphene and lithium titanate composite materials, the problem of insufficient conductivity of lithium titanate is solved, and the specific capacity and cycling performance of the material are significantly improved. It is suitable for lithium-ion batteries in high-magnification and high-low temperature environments.
Patent Information
- Application Number
- CN202411287954.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-13
AI Technical Summary
The existing methods have limited improvements in the conductivity of lithium titanate and have not significantly improved the comparative capacity, making it difficult to meet the needs of high rate performance and cycle stability.
The modified lithium titanate composite material is prepared by composited graphene and nitrided lithium titanate. The nanoparticle size preparation, nitriding treatment and graphene coating are improved to improve the conductivity and specific capacity of lithium titanate.
It significantly improves the conductivity and specific capacity of lithium titanate materials, achieves high-rate performance, excellent cycle performance and high-low temperature performance, and is suitable for power-type lithium-ion batteries.
Smart Images

Figure CN119118194A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of rechargeable lithium-ion batteries, and in particular to a modified lithium titanate composite material, a preparation method thereof, and a lithium-ion battery. Background Art
[0002] At present, the research focus of negative electrode materials for lithium-ion batteries is developing towards power battery materials with high specific capacity, high rate, high cycle performance and high safety performance. The traditional negative electrode material is carbon negative electrode material. Although carbon negative electrode has been successfully commercialized, its battery safety problems, especially safety problems at high rates, force people to look for new safe and reliable negative electrode materials that can embed lithium at a slightly positive potential than carbon negative electrode. Among them, low-potential transition metal oxides and composite oxides have attracted widespread attention as negative electrode materials for lithium-ion batteries, especially the zero-strain material Li4Ti5O12, which has attracted widespread attention for its 1.5V (vs. Li / Li+) voltage, charge and discharge efficiency close to 1 and excellent cycle performance. It is a very potential electrode material as a negative electrode material for power lithium-ion batteries.
[0003] However, the electronic conductivity of lithium titanate is poor, which limits its high-rate performance. Therefore, it is necessary to improve its conductivity by modifying it, so as to improve the high-rate performance of lithium titanate to meet the needs of power batteries, and it is necessary to maintain its high reversible electrochemical capacity and good cycle stability. At present, the methods that can improve the rate performance of lithium titanate mainly include: preparing lithium titanate with nano-particle size, doping lithium titanate body and introducing conductive phase. The existing method of carbon coating lithium titanate has a certain improvement in its performance, but the improvement in its conductivity is limited and the specific capacity is not improved. The movement speed of electrons in graphene reaches 1 / 300 of the speed of light, which far exceeds the movement speed of electrons in general conductors. It is an excellent electronic conductor, and graphene itself has a high lithium storage specific capacity. Therefore, compounding lithium titanate and graphene to prepare graphene-based lithium titanate composite electrode materials will greatly improve the conductivity of lithium titanate materials and effectively improve the specific capacity of materials. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a modified lithium titanate composite material and a preparation method thereof and a lithium ion battery, aiming to solve the problem that the existing method of carbon coating lithium titanate has a certain improvement in its performance, but has limited improvement in its conductivity and no improvement in specific capacity. The technical solution of the present invention is as follows: A method for preparing a modified lithium titanate composite material, comprising the following steps: (1) Preparation of nano lithium titanate powder: dissolving a lithium source and a titanium source in a solvent respectively, mixing the two solutions and adding acetic acid; heating to 40-100°C, stirring at a constant temperature for 4-10 hours; drying at 80-120°C to obtain a precursor; dispersing the precursor in deionized water, spray drying to obtain a powder; calcining the powder at 700-1000°C for 6-18 hours; cooling and grinding to obtain nano lithium titanate powder; (2) Preparing lithium titanate nitride powder: heating the obtained nano lithium titanate powder to 700-1000° C. in a nitrogen atmosphere for nitridation treatment for 5-10 hours to obtain lithium titanate nitride powder; (3) Preparation of graphene oxide: natural flake graphite and sodium nitrate are mixed, concentrated sulfuric acid is added, and the mixture is stirred in an ice-water bath for 10 to 20 minutes. Potassium permanganate is then added, and the mixture is reacted in an ice-water bath for 0.5 to 1 hour. After stirring at 20 to 25°C for 24 to 48 hours, deionized water and hydrogen peroxide are added to react for 10 to 20 minutes, and centrifuged. The separated product is washed, centrifuged, and dried to obtain graphene oxide. (4) Preparation of modified lithium titanate composite material: The prepared lithium titanate nitride powder and graphene oxide are evenly mixed, and calcined at 700 to 1100° C. for 3 to 10 min in an inert atmosphere or a reducing atmosphere to obtain a modified lithium titanate composite material. The preparation method, wherein in step (1), the lithium source is one or a mixture of two or more of lithium hydroxide, lithium acetate and lithium nitrate; and the titanium source is tetrabutyl titanate or tetraisopropyl titanate.
[0005] The preparation method, wherein in step (1), the molar ratio of Li to Ti in the lithium source and the titanium source is 0.8 to 0.86.
[0006] The preparation method, wherein in step (2), the nitrogen atmosphere is ammonia or a nitrogen-hydrogen mixture.
[0007] The preparation method, wherein in step (3), the mass ratio of sodium nitrate to natural flake graphite is 1:1, the mass ratio of the volume of concentrated sulfuric acid to the mass ratio of natural graphite flakes is 50-60 mL / g, and the mass ratio of potassium permanganate to natural flake graphite is 6:1.
[0008] The preparation method, wherein in step (3), the concentration of the hydrogen peroxide is 30wt%, the volume ratio of the hydrogen peroxide to the mass ratio of the natural flake graphite is 20-30mL / g; the volume ratio of the deionized water to the mass ratio of the natural flake graphite is 75-100mL / g.
[0009] The preparation method, wherein in step (4), the reducing atmosphere is a nitrogen-hydrogen mixture.
[0010] The preparation method, wherein in step (4), the graphene oxide accounts for 1.0 to 19.4 wt % of the mixture of lithium titanate nitride powder and graphene oxide.
[0011] The preparation method, wherein in step (4), in the modified lithium titanate composite material, the graphene material accounts for 1.0 to 18.1 wt % of the modified lithium titanate composite material.
[0012] A modified lithium titanate composite material is prepared by the preparation method of the present invention.
[0013] A lithium ion battery comprises a negative electrode, wherein the material of the negative electrode is the modified lithium titanate composite material described in the present invention.
[0014] Beneficial effects: Compared with the prior art, the present invention double-modifies lithium titanate by doping and coating, and specifically uses graphene with extremely high electronic conductivity and nitrogen-doped lithium titanate to prepare modified lithium titanate electrode materials. The preparation process is simple and flexible, and the lithium titanate used can be synthesized by any method without affecting the performance of the composite material, and can be applied to the modified production of existing lithium titanate materials. The prepared modified lithium titanate composite material has large rate performance, excellent cycle performance and high and low temperature performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The XRD patterns of the lithium titanate and modified lithium titanate composite materials prepared in Example 1 and the modified lithium titanate composite materials prepared in Example 2, wherein (a) is the XRD spectrum of the spinel lithium titanate prepared according to the method described in Example 1; (b) is the XRD spectrum of the modified lithium titanate composite material prepared according to the method described in Example 1; (c) is the XRD spectrum of the modified lithium titanate composite material prepared according to the method described in Example 2; Figure 2 The first charge-discharge curve of the modified lithium titanate composite material at 0.2C obtained in Example 1; Figure 3 This is the first charge and discharge curve of the modified lithium titanate composite material 5C prepared in Example 2; Figure 4 This is a cycle performance diagram of the modified lithium titanate composite material prepared in Example 2 at 5C; Figure 5 This is a cycle performance diagram of the modified lithium titanate composite material obtained in Example 3 at 10C; Figure 6 is a graph showing the graphene content and the first discharge specific capacity (5C) of the modified lithium titanate composite material in Examples 2, 3 and 5; DETAILED DESCRIPTION Embodiment 1
[0016] Weigh 3.9975g of anhydrous lithium acetate and 23.9539g of tetrabutyl titanate in a molar ratio of Li:Ti=0.86:1. Use ethanol as a dispersant to dissolve anhydrous lithium acetate and tetrabutyl titanate in ethanol respectively. Mix the two solutions under stirring, and then add 10mL of acetic acid. Stir at a constant temperature of 80°C for 4 hours, and dry at 120°C to obtain a precursor. Disperse the precursor in deionized water to form a suspension, and spray-dry the suspension to obtain a powder, with the hot air temperature being 140°C. Heat the powder to 800°C at 5°C / min in a muffle furnace, keep the temperature constant for 12h, cool naturally to room temperature, grind, and pass through a 150-mesh sieve to obtain nano lithium titanate powder. X-ray powder diffraction (XRD) test shows that it is a nano lithium titanate powder with a single spinel structure, see Figure 1 Middle a.
[0017] The obtained nano lithium titanate powder was heated to 700° C. in a nitrogen-hydrogen mixed gas (hydrogen accounting for 5 vol%) for nitridation treatment for 10 hours to obtain nitrided lithium titanate powder.
[0018] Mix 2.0002g natural flake graphite and 2.0036g sodium nitrate, add 116mL concentrated sulfuric acid solution, stir in an ice-water bath for 10min, then slowly add 12.0728g potassium permanganate to the solution, react in an ice-water bath for 0.5h, stir continuously at 20℃ for 48h, add 184mL deionized water, 40mL hydrogen peroxide (30wt%), react for 20min, and centrifuge. The separated product is washed three times with a mixed solution of sulfuric acid and hydrogen peroxide (sulfuric acid accounts for 6wt%, hydrogen peroxide accounts for 1wt%) and deionized water, then centrifuge and vacuum dry to obtain graphene oxide.
[0019] 2.3960g of prepared lithium titanate nitride powder and 0.0821g of graphene oxide were mixed evenly and calcined in a nitrogen atmosphere at a temperature of 1000°C for 3 min to obtain a modified lithium titanate composite material. The graphene accounted for 3.204wt% of the total mass of the modified lithium titanate composite material. After XRD testing, it still had a spinel structure. Figure 1 Middle b.
[0020] The electrochemical test was carried out under the following conditions: the prepared modified lithium titanate composite material was used as the active material, SuperP (super carbon) as the conductive agent, PVDF (polyvinylidene fluoride) as the binder, and NMP (N-methyl-2-pyrrolidone) as the solvent to prepare the slurry and apply it on the copper foil to make the pole piece. The test cell was assembled with lithium sheet as the electrode, the electrolyte concentration was 1 mol / L, and the polypropylene microporous membrane was used as the battery diaphragm. The button cell was assembled in a glove box filled with argon gas for electrochemical testing. The charge and discharge voltage range was 1.0 to 2.5V.
[0021] The product was assembled into a battery according to the above method. The first discharge capacity at 0.2C was 192.8mAh / g and the charge capacity was 176.9mAh / g. Figure 2 shown. Embodiment 2
[0022] Weigh 4.3015g of anhydrous lithium acetate and 27.2309g of tetrabutyl titanate at a molar ratio of Li:Ti=0.81:1, use ethanol as a dispersant, dissolve anhydrous lithium acetate and tetrabutyl titanate in ethanol respectively, mix the two solutions under stirring, and add 10mL of acetic acid. Stir at a constant temperature of 40°C for 10 hours, and dry the precursor at 80°C. Disperse the precursor in deionized water to form a suspension, and spray dry the suspension to obtain a powder, and the hot air temperature is 140°C. The powder is heated to 1000°C at 5°C / min in a muffle furnace, kept at a constant temperature for 6h, naturally cooled to room temperature, ground, and sieved through a 150-mesh sieve to obtain nano lithium titanate powder.
[0023] The obtained nano lithium titanate powder was heated to 800° C. in an ammonia atmosphere for nitridation treatment for 5 hours to obtain nitrided lithium titanate powder.
[0024] Mix 2.0006g natural flake graphite and 2.0021g sodium nitrate, add 120mL concentrated sulfuric acid solution, stir in an ice-water bath for 15min, then slowly add 12.0036g potassium permanganate to the solution, react in an ice-water bath for 1h, stir continuously at 25°C for 36h, add 150mL deionized water, 50mL hydrogen peroxide (30wt%), react for 15min, and centrifuge. The separated product is washed three times with a mixed solution of sulfuric acid and hydrogen peroxide (sulfuric acid accounts for 6wt%, hydrogen peroxide accounts for 1wt%) and deionized water, then centrifuge and vacuum dry to obtain graphene oxide.
[0025] 2.0164g of prepared lithium titanate nitride powder and 0.0742g of graphene oxide were mixed evenly, and calcined in a nitrogen-hydrogen mixed gas (hydrogen accounted for 10vol%) atmosphere at a temperature of 800°C for 10min to obtain a modified lithium titanate composite material. Graphene accounted for 3.241wt% of the total mass of the modified lithium titanate composite material. XRD test showed that the crystal form did not change, as shown in FIG. Figure 1 Indicated in c.
[0026] The obtained product was assembled into a battery according to the method of Example 1. The first discharge capacity at 5C was 159.0 mAh / g, and the charge capacity was 153.2 mAh / g. Figure 3 And the cycle performance is good, the capacity is not less than 123.4mAh / g after 100 cycles, as shown in Figure 4Example 3 This embodiment 1 provides a composite manganese oxide compound film and a preparation method thereof. The composite manganese oxide compound film is prepared according to a method comprising the following steps: S11: Use a copper plate with a diameter of 70 mm as a tray for the powder target, evenly spread the manganese trioxide powder in the tray, and use a 5-ton unidirectional press to perform unidirectional dry pressing to obtain the manganese trioxide powder target; S12: The manganese trioxide powder target prepared in step S11 and a purchased tin ceramic target with a purity of 99.999% are used as sputtering sources. On a Japanese 304 stainless steel substrate, the substrate-target distance is 50 mm. In a mixed atmosphere of high-purity ammonia and oxygen at 1.0×10-2 mbar, a co-sputtering method with a power ratio of Mn2O3:Sn=1:4 is used to prepare a Mn2O3-Sn composite film with a thickness of 1 μm; during deposition, the substrate is maintained at 200°C. Embodiment 3
[0027] Other conditions are the same as those in Example 1, except that the mixture of lithium titanate nitride powder and graphene oxide contains 5.8221 g of lithium titanate powder and 0.0612 g of graphene oxide, and is calcined in a nitrogen-containing atmosphere at a temperature of 1000°C for 30 min to obtain a modified lithium titanate composite material, in which graphene accounts for 1.011 wt% of the total mass of the modified lithium titanate composite material.
[0028] The obtained product was assembled into a battery according to the method of Example 1. The initial charge and discharge capacity at 5C was about 150 mAh / g, and the capacity after 100 cycles was about 110 mAh / g. Embodiment 4
[0029] Other conditions are the same as those in Example 2, except that the mixture of lithium titanate nitride powder and graphene oxide contains 0.5071 g of lithium titanate powder and 0.1201 g of graphene oxide, and is calcined in a nitrogen-hydrogen mixed gas atmosphere (hydrogen accounts for 5 vol%) at a temperature of 900°C for 30 minutes to obtain a modified lithium titanate composite material, in which graphene accounts for 18.102 wt% of the total mass of the modified lithium titanate composite material.
[0030] The obtained product was assembled into a battery according to the method of Example 1. The initial charge and discharge capacity at 5C was as high as 130 mAh / g. After 100 cycles, the capacity was not less than 100 mAh / g. Figure 6 It is a curve diagram of the graphene content and the first discharge specific capacity (5C) of the modified lithium titanate composite material in Examples 2, 3 and 5.
[0031] In summary, the present invention provides a modified lithium titanate composite material, a preparation method thereof, and a lithium ion battery. Compared with the prior art, the present invention uses graphene with extremely high electronic conductivity and nitrided lithium titanate to prepare a modified lithium titanate composite material. The preparation process is simple and flexible. The lithium titanate used can be synthesized by any method without affecting the performance of the composite material, and can be applied to the modified production of existing lithium titanate materials. The prepared modified lithium titanate composite material has a large rate performance, excellent cycle performance and high and low temperature performance. The first charge and discharge capacity at 10C is still 180mAh / g, and the charge and discharge cycle is 10,000 times. The reversible capacity decay is less than 20%, and it can work in the range of -40~60℃. The prepared modified lithium titanate composite material can be widely used in lithium ion batteries required for various portable electronic devices and various electric vehicles.
[0032] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a modified lithium titanate composite material, characterized in that: The following steps are involved: (1) Preparation of nano lithium titanate powder: dissolving a lithium source and a titanium source in a solvent respectively, mixing the two solutions and adding acetic acid; heating to 40-100°C, stirring at a constant temperature for 4-10 hours; drying at 80-120°C to obtain a precursor; dispersing the precursor in deionized water, spray drying to obtain a powder; calcining the powder at 700-1000°C for 6-18 hours; cooling and grinding to obtain nano lithium titanate powder; (2) Preparing lithium titanate nitride powder: heating the obtained nano lithium titanate powder to 700-1000° C. in a nitrogen atmosphere for nitridation treatment for 5-10 hours to obtain lithium titanate nitride powder; (3) Preparation of graphene oxide: natural flake graphite and sodium nitrate are mixed, concentrated sulfuric acid is added, and the mixture is stirred in an ice-water bath for 10 to 20 minutes. Potassium permanganate is then added and the mixture is reacted in an ice-water bath for 0.5 to 1 hour. After stirring at 20 to 25°C for 24 to 48 hours, deionized water and hydrogen peroxide are added and the mixture is reacted for 10 to 20 minutes, and then centrifuged; The separated product is washed, centrifuged and dried to obtain graphene oxide; (4) Preparation of modified lithium titanate composite material: The prepared lithium titanate nitride powder and graphene oxide are uniformly mixed, and calcined at 700 to 1100° C. in an inert atmosphere or a reducing atmosphere for 3 to 10 min to obtain a modified lithium titanate composite material.
2. The preparation method according to claim 1, characterized in that: In step (1), the lithium source is one or a mixture of two or more of lithium hydroxide, lithium acetate and lithium nitrate; the titanium source is tetrabutyl titanate or tetraisopropyl titanate; and the molar ratio of Li to Ti in the lithium source and the titanium source is 0.8 to 0.
86.
3. The preparation method according to claim 1, characterized in that: In step (2), the nitrogen atmosphere is ammonia or a nitrogen-hydrogen mixture.
4. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of sodium nitrate to natural flake graphite is 1:1, the mass ratio of concentrated sulfuric acid to natural graphite flake is 50-60 mL / g, and the mass ratio of potassium permanganate to natural flake graphite is 6:
1.
5. The preparation method according to claim 1, characterized in that: In step (3), the concentration of the hydrogen peroxide is 30wt%, the volume ratio of hydrogen peroxide to the mass ratio of natural flake graphite is 20-30mL / g; the volume ratio of deionized water to the mass ratio of natural flake graphite is 75-100mL / g.
6. The preparation method according to claim 1, characterized in that: In step (4), the reducing atmosphere is a nitrogen-hydrogen mixture.
7. The preparation method according to claim 1, characterized in that: In step (4), the graphene oxide accounts for 1.0 to 19.4 wt % of the mixture of lithium titanate nitride powder and graphene oxide.
8. The preparation method according to claim 1, characterized in that In step (4), in the modified lithium titanate composite material, the graphene material accounts for 1.0 to 18.1 wt % of the modified lithium titanate composite material.
9. A modified lithium titanate composite material, characterized in that: The method is prepared by any one of claims 1 to 8.
10. A lithium ion battery comprising a negative electrode, characterized in that: The material of the negative electrode is the modified lithium titanate composite material as described in claim 9.
